Big experimenter is watching you! Anonymity and prosocial behavior in the laboratory - Franziska Barmettler; Ernst Fehr; Christian Zehnder (University of Zurich, Department of Economics, 2011)
Social preference research has received considerable attention in recent years. Researchers have demonstrated that the presence of people with other-regarding preferences can have important implications in many economic dimensions. However, it is important to be aware of the fact that the empirical basis of this literature relies to a large extent on experiments that do not provide anonymity between experimenter and subject. It has been argued that this lack of experimenter-subject anonymity may create selfish incentives to engage in seemingly other-regarding behavior. If this were the case these experiments would overestimate the importance of social preferences. Previous studies provide mixed results and methodological differences within and across studies make it difficult to isolate the impact of experimenter-subject anonymity on prosocial behavior. In this paper we use a novel procedure that allows us to examine the impact of the exact same ceteris-paribus variation in anonymity on behavior in three of the most commonly used games in the social preference literature. Our data reveals that introducing experimenter-subject anonymity has only minor, insignificant, effects on prosocial behavior.
Keywords: C91; D03; 330; scrutiny; anonymity; laboratory experiments; prosocial behavior; Soziale Wohlfahrtsfunktion; Verhaltensökonomik; Test